Identifying Plant Age to Determine Production Trend of Oil Palm Fresh Fruit Bunches - M Juremi Suhartono; Heri Setyawan; Wandha Atmaka Aji (Agro Bali : Agricultural Journal, 2023)
The productivity management of oil palm plantations is carried out by analyzing various influencing factors, but the growing conditions of oil palms are one of the causes of fluctuations in oil palm production. This paper aims to identify post-harvest increases in oil palm productivity. Productivity depends on the number of clusters and the weight of fresh fruit bunches (FFB) produced yearly. The methods of this study were conducted using a targeted sampling technique using available production data for plant time points from 4 to 13 years of age. The total plant sample was 636 ha in Central Kalimantan. As a result, plant growth factors can significantly impact oil palm productivity as measured by the components of oil palm plant production: fresh bunch production per hectare, average bunch weight, and the number of oil palm bunches. FFB tonnage and mean bunch weight increase each year from age 3 to age 13, according to a quadratic regression pattern, whereas the number of palm clusters, in contrast, decreases in number with increasing plant age. This study was intended to serve as a reference and source of information for making production decisions for oil palm plantations to achieve optimal results.